Gene Therapy Medicinal Products: Non-clinical Safety Studies - O. V. Astapova; A. A. Berchatova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
Currently, gene therapy medicinal products (GTMPs) are actively developed in many countries, including the Russian Federation. However, the use of GTMPs raises class-specific safety concerns.The aim of the study was to determine the main requirements for non-clinical safety testing of GTMPs, to identify risks associated with these medicinal products, to establish criteria for expert assessments, and to find optimisation opportunities for GTMP non-clinical safety programmes, using Russian and international experience in the assessment of submissions and the registration of medicinal products of this class.The Russian Federation, the Eurasian Economic Union, the European Union, and the United States have created regulatory frameworks governing the lifecycle of GTMPs and continue improving these frameworks. The properties of GTMPs may create unique safety issues, such as insertional mutagenesis, unregulated transgene expression, long-term persistence and off-target spread, vertical germline transmission, and environmental risks. To account for these issues, a comprehensive non-clinical safety programme for GTMPs may require additional special studies along with the standard ones. This review focuses on the main approaches to designing non-cellular GTMP safety studies and evaluating the obtained results. The authors identified improvement opportunities for and problematic aspects of study design, as well as conditions for and limitations of non-clinical data extrapolation and clinical safety profile prediction. The continuous improvement and updating of the regulatory frameworks governing non-clinical studies of GTMPs mean that developers of non-clinical safety programmes for GTMPs should use all their experience, as well as relevant national and international guidelines and recommendations.